2018
DOI: 10.1109/tgrs.2017.2755506
|View full text |Cite
|
Sign up to set email alerts
|

Radar Propagation Experiment in the North Sea: The Sylt Campaign

Abstract: Abstract-This paper describes an experiment that was carried out in the North

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
(3 reference statements)
0
4
0
Order By: Relevance
“…On the one hand, maritime communication faces challenges such as long distances between BSs and users, significant transmission delays, and high interference [17]. It is difficult to obtain the CSI in the maritime environment [18], and the traditional communication resource allocation schemes based on CSI are difficult to employ in the maritime environment [19]. On the other hand, there is still a lack of relevant research on the distribution characteristics of communication users in maritime environments.…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, maritime communication faces challenges such as long distances between BSs and users, significant transmission delays, and high interference [17]. It is difficult to obtain the CSI in the maritime environment [18], and the traditional communication resource allocation schemes based on CSI are difficult to employ in the maritime environment [19]. On the other hand, there is still a lack of relevant research on the distribution characteristics of communication users in maritime environments.…”
Section: Introductionmentioning
confidence: 99%
“…It reported a σ o value for the maximum observed peak of -24.5 dB. In [6], a very comprehensive trial (North Sea Sylt campaign) was reported which encompassed meteorological and oceanographic sensor data along with radar measurements at X, Ka and W bands. In terms of radar sea clutter, it presented range-time intensity plots from X and Ka-band data, but no amplitude or Doppler characteristics analysis at W-band were reported.…”
Section: Introductionmentioning
confidence: 99%
“…An atmospheric duct is a unique phenomenon in the lower atmosphere, and electromagnetic waves can experience less attenuation in the trapped layer by limiting the spread of the wavefront from spherical to cylindrical expansion, where the waves are bent by atmospheric refraction [1,2]. A long-range transmission in microwave bands can also be realized.…”
Section: Introductionmentioning
confidence: 99%